Persuading in Arabic and English: A Study of EFL Argumentative Writing in Contrast with Native English Norms - El-Dakhs, Dina Abdel Salam; Yahya, Noorchaya; Al Thowaini, Buthainah M. (Open Cultural Studies, 2025)
This study investigated the use of persuasive strategies in argumentative academic writing by Arabic–English bilingual English as a foreign language (EFL) learners in their second language (English, L2), compared to their first language (Arabic, L1) and English L1 writing by native speakers of English. This tripartite comparison between bilinguals’ L1 and L2 writing and English native speakers’ writing is a key contribution of the study since it allows us to consider how persuasion is employed in the participants’ L2 in light of two baselines of comparisons. To this end, 60 Saudi undergraduates wrote argumentative paragraphs in English and Arabic, and these paragraphs were compared against one another and also against English argumentative paragraphs by American undergraduates for the use of persuasive strategies. The findings revealed statistically significant differences in the use of persuasive strategies across the three groups of paragraphs. While the EFL learners tended to employ logos and pathos strategies more frequently in their L1 and L2 writing than English Native Speakers (NS), the NS, in turn, produced significantly more ethos strategies than the EFL learners. The differences were most noted in the use of logos strategies involving logical reasoning, pathos strategies – such as evaluative expressions and fostering collegiality – and ethos strategies, including demonstrating involvement, sharing personal perspectives, and modulating commitment to claims and community use. In addition, the results showed that increased English language proficiency had a limited effect on the use of persuasive strategies by EFL learners in their English writing.